Special Library Versus Specialist Library - Ranganathan, S. R.; Gopinath, M. A. (Journal of Information and Knowledge, 2002)
This is a report of two classes in DRTC, extending over three hours, conducted by Dr Ranganathan, on 19 and 20 March 1967. Traces the origin of the term 'Special Library'. Shows that the term 'Special Library' is a homonym and thus it does not precisely connote the emphasis on the service of nascent micro documents to specialists. Shows that the term 'Specialist Library' directly and precisely lays emphasis on the service of 'I'. nascent micro documents to specialists. Incidentally points out the need for and importance of giving a precisely expressive unique name for a concept in a discipline. Annotations are added explaining the educational principles demonstrated by the work in the class.